2020
DOI: 10.1002/jor.24579
|View full text |Cite
|
Sign up to set email alerts
|

In vitro evaluation of human myoblast function after exposure to cobalt and chromium ions

Abstract: The replacement of a native hip joint by a metal‐on‐metal prosthesis may induce deleterious inflammatory side effects that are associated with the release of wear particles and metal ions. These events are referred to the adverse reaction to metal debris (ARMD) and the adverse local tissue reaction (ALTR). While wear particles seem involved in ARMD, the role of metal ions in ALTR and their impact on myoblasts, located in the prosthesis vicinity, has not been fully identified. To clarify this issue we investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Metal ions can be released by multiple mechanisms: (a) wear‐mediated disruption of the passive layer on the implant surface, (b) release of metal ions from nano‐ and micron‐sized particles in body fluids, (c) cellular reactions—especially in the lysosomes—to the phagocytized particles generate metal ions that can be released into the periprosthetic tissue 25 . Several studies have shown the inflammatory and osteolytic effect of cobalt and chromium ions 30,31 . The presence of elevated metal ions in synovial fluid and serum has been associated with the development of adverse local reactions in periprosthetic tissue 32 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metal ions can be released by multiple mechanisms: (a) wear‐mediated disruption of the passive layer on the implant surface, (b) release of metal ions from nano‐ and micron‐sized particles in body fluids, (c) cellular reactions—especially in the lysosomes—to the phagocytized particles generate metal ions that can be released into the periprosthetic tissue 25 . Several studies have shown the inflammatory and osteolytic effect of cobalt and chromium ions 30,31 . The presence of elevated metal ions in synovial fluid and serum has been associated with the development of adverse local reactions in periprosthetic tissue 32 .…”
Section: Discussionmentioning
confidence: 99%
“…25 Several studies have shown the inflammatory and osteolytic effect of cobalt and chromium ions. 30,31 The presence of elevated metal ions in synovial fluid and serum has been associated with the development of adverse local reactions in periprosthetic tissue. 32 A previous study demonstrated a strong correlation between elevated metal ion concentrations and patients with ALTR.…”
Section: Discussionmentioning
confidence: 99%
“…This cytotoxicity has been observed in various cell types, including human cell lines and primary cells. 57,58 Nonetheless, since CoCrMo is an established material used in spinal implants, obtaining a comparable cell viability with the extracts from the SiFeCN coatings is considered a promising result, indicating that further evaluation of these materials is warranted.…”
Section: Paper Biomaterials Sciencementioning
confidence: 99%
“…These metal ions are increasingly recognized as both local and systemic toxins based on the alterations to native host tissues they produce and due to the increased migration of T lymphocytes caused by Co and Cr ions. [8][9][10] There is evidence that the local toxicity of these ions is associated with adverse local tissue reaction (ALTR), adverse reaction to metal debris (ARMD), inflammatory pseudotumor, and local osteolysis. 11,12 Although these diseases may partly explain the higher revision rates of MoP prosthesis, no conclusive evidence exist on the risk of PJI associated with these implants.…”
mentioning
confidence: 99%